A Comparative Study of Ionization of Hydrogenic Ions by Positronium Impact (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
A comparative study of target ionization processes of Hydrogenic ions by Positronium impact are investigated. Calculations are performed using the Coulomb distorted eikonal approximation. Interesting qualitative features are noted both in the scattered Ps and the ejected electron distributions in triple differential as well as double differential cross sections. The Ps impact ionization of three hydrogenic ions shows some distinct variation from the electron impact ionization.